Archaeometallurgical studies on corrosion behaviour of Cu-As alloys from "Lama" (2nd millennium BC), Iran - Mohammadamin Emami; Javad Jafari (UISPP Journal)
The Lama cemetery is located in west of the Zagros Mountains in Iran. The excavated materials are bronze objects, silver rings, iron items and pottery that were scattered in the graves. Pottery with continuous painted lines and triangular patterns and metal tools were the main evidence for dating the cemetery to the Middle Elamite II, III and Neo-Elamite I periods (1400-800 BC). The objects were analyzed by means of ICP-OES, OM and SEM-EDX in order to obtain data on the metal composition and alloying process. The results show various compositions concerning the Cu/Sn ratio in the metallic core of the objects. The variety of tin content proves that the objects were not made by using a particular proportion of alloying elements. An uncontrolled process was used to produce tin bronze, such as co-smelting, cementation, recycling or smelting copper- tin bearing ores.